Pogram Pembelajaran bahasa Arab terhadap mahasiswa USIM Malaysia di Universitas Darussalam Gontor - Achmad Farouq Abdullah; Hendro Risbiyantoro; Samiyono; Afaf Saifullah Kamalie (Jurnal Pengabdian Masyarakat (Bisma), 2025)
This study examines the significance of Arabic language acquisition in enhancing communicative competence and deepening comprehension of Islamic literary sources, particularly the Qur'an and Hadith. Through a structured training program involving 10 students at Universiti Sains Islam Malaysia (USIM), the research employed a mixed-methods approach combining quantitative and qualitative analysis. The intervention featured diagnostic pre-tests, instructional delivery, and summative post-tests, supplemented by structured participant feedback. Results demonstrated statistically significant improvements in oral proficiency, though identified temporal constraints and material coverage limitations as key challenges. The study proposes extending program duration and developing more interactive pedagogical resources for future implementations. These findings contribute to Arabic language pedagogy by offering a replicable instructional model with potential applications across higher education institutions, while emphasizing the importance of sustained professional development for optimal language acquisition outcomes.